Lactobacillus spp. effect evaluation in the small intestine development in broiler chickens - Rodríguez-González, Sandra Paola; Moreno-Figueredo, Giovanni (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The probiotic Lactobacillus spp. type, are considered promising alternatives to replace the use of antibiotics as growth promoters (APC) in poultry farms, due to their influence in the gastrointestinal tract (GIT) poseclosion development and in their microbial ecology. Thereof in this study the morphometry of the small intestine in broilers to provide with 0.5 mL/L of a commercial product based on Lactobacillus spp. were evaluated. 200 male chickens a day old, from the Cobb Avian 48 line were used, distributed under a completely randomized design, in two groups, called control and experiment. Both groups were kept in similar conditions of feeding, management and health care.At 7, 15 and 35 days old sacrifice and necropsy was performed. Segments from duodenum, jejunum and ileum were dissected for processing with the hematoxylin-eosin (H-E) coloration technique. The villi morphometric changes in length, width and number were assessed using a trinocular microscope with digital camera Moticam®. Data were analyzed using SPSS version 19 program. Comparisons of averages were conducted through descriptive statistics and ANOVA (p < 0.05) test. Significant differences (p <0.05l were estimated in favor ofthe poseclosion development experiment group ofthe jejunum and ileum segments.